DINAMIKA PESANTREN KONTEMPORER - Syamsul Ma’arif (Millah: Journal of Religious Studies, 2011)
This article will explain about the contemporary developments in the pesantren (Islamic boarding schools), especially its role in maintaining the tradition and stem infiltration of religious radicalism at the pesantren. The steps that can be used by pesantren is by teaching inclusive faith and the reformulation of multicultural curriculum for the students (santri). All this, with consideration for each movement by fundamentalists and extremists who cast a "jihad" to fight against those who disagree actually do not fit with the character and cultural of the pesantren. Is not the pesantren has always showed his attitude that it is always accommodating and understanding of diversity?